2012
DOI: 10.1016/j.jcrysgro.2012.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Growth and characterization of epitaxial Ti3GeC2 thin films on 4H-SiC(0001)

Abstract: Epitaxial Ti 3 GeC 2 thin films were deposited on 4° off-cut 4H-SiC(0001) using magnetron sputtering from high purity Ti, C, and Ge targets. Scanning electron microscopy and helium ion microscopy show that the Ti 3 GeC 2 films grow by lateral step-flow with {11 2 0} faceting on the SiC surface. Using elastic recoil detection analysis, atomic force microscopy, and X-Ray diffraction the films were found to be substoichiometric in Ge with the presence of small Ge particles at the surface of the film.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
(38 reference statements)
2
5
0
Order By: Relevance
“…vacancies and stacking faults), which are most likely in the A layer. Very recent experimental studies on Ti 3 GeC 2 thin films have suggested samples to be Ge deficient, 29 which was also postulated to be responsible for the high damping measured through RUS. 13 To explore this, the estimated ADPs for Ti 3 GeC 2 with Ge vacancies are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…vacancies and stacking faults), which are most likely in the A layer. Very recent experimental studies on Ti 3 GeC 2 thin films have suggested samples to be Ge deficient, 29 which was also postulated to be responsible for the high damping measured through RUS. 13 To explore this, the estimated ADPs for Ti 3 GeC 2 with Ge vacancies are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One possibility, always present, is sample-to-sample variations. Other possibilities are secondary phases and effects of non-stoichiometry, the latter known to occur for several other MAX phases [25,49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The total average for the (Cr2/3Ti1/3)3AlC2 phase across all samples remains 25.0 ± 2.1 at% (σ = 0.9%). Amongst MAX phases, one can easily find works where non-stoichiometries were measured [1,[42][43][44][45][46][47] or suggested according to DFT calculations [20,[47][48][49][50][51]. As in most if not all cases an X or A elemental deficiency was reported (e.g.…”
mentioning
confidence: 99%
“…As in most if not all cases an X or A elemental deficiency was reported (e.g. Ti4AlN2.9 [44,45], Ti3Ge0.8C2 [42]) it appears reasonable to make the assumption that M sites in (Cr2/3Ti1/3)3AlC2 are fully occupied and that this can serve as the necessary reference for stoichiometry determination. Thereby, as the Al/(Al+Ti+Cr) ratio stays very close to 25 at% throughout the measurement sessions and the samples, it can be concluded that EDX, in the limit of its sensitivity, was not able to evidence any deficiency (or excess) in Al and the stoichiometry of Al in (Cr2/3Ti1/3)3AlC2 is therefore expected to be exactly 1, regardless of the initial reactants stoichiometries.…”
mentioning
confidence: 99%